2018
DOI: 10.29309/tpmj/18.4553
|View full text |Cite
|
Sign up to set email alerts
|

Goiter;

Abstract: The object of this study was to observe prevalence of Goiter disorder and to classify the Goiter patients regarding sex, age and find various conditions of goiter patient in different talukas of district Sukkur, Sindh, Pakistan. Introduction: Thyroid gland is the largest organ of the endocrine system, located in the region of neck. Thyroid disease is a condition that disturbs the function of the thyroid gland. Over activity of thyroid gland to release excess quantity of hormones is called hyperthyroidism and u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 3 publications
2
1
0
Order By: Relevance
“…In a similar Pakistani study, Anwar et al (2012) reported results matching with our findings as frequency of patients with age >50 years was 11.8%, 25-50 years were 52.0% and less than 25 years age were 36.2%. 16 Age distribution reported in MNG patients by Saqlain et al (2018) also supports our findings. 22 Shrestha et al (2014) also reported comparable frequency in Nepali population as 22.0% with age <25 years, 64.0% had age range of 25-50 years while their remaining 14.0% study population had age >50 years.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…In a similar Pakistani study, Anwar et al (2012) reported results matching with our findings as frequency of patients with age >50 years was 11.8%, 25-50 years were 52.0% and less than 25 years age were 36.2%. 16 Age distribution reported in MNG patients by Saqlain et al (2018) also supports our findings. 22 Shrestha et al (2014) also reported comparable frequency in Nepali population as 22.0% with age <25 years, 64.0% had age range of 25-50 years while their remaining 14.0% study population had age >50 years.…”
Section: Discussionsupporting
confidence: 86%
“…16 Age distribution reported in MNG patients by Saqlain et al (2018) also supports our findings. 22 Shrestha et al (2014) also reported comparable frequency in Nepali population as 22.0% with age <25 years, 64.0% had age range of 25-50 years while their remaining 14.0% study population had age >50 years. 23 Hossain et al (2014) in Bangla reported frequency for these age slabs as 24.0%, 66.0% and 10.0% respectively.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation